Efektivitas Penggunaan Ruang Warna HSV untuk Klasifikasi Daging Sapi Segar dan Busuk dalam Industri Pangan - Dadang Iskandar Mulyana; Veri Arinal; Feri Akbarulloh (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Beef is a source of animal protein which is very important in the human diet. The quality of beef determines the nutritional value and taste of the processed meat product. However, the quality of beef can decrease over time, especially if it is not stored properly. Therefore, identifying the condition of beef is crucial to ensure that consumers get safe and quality products. The use of the HSV (Hue, Saturation, Value) color space for beef classification is an interesting method to research. The HSV color space is closer to human perception of color compared to the RGB color space, making it more effective for image analysis in the context of visual quality assessment of meat. In this study, researchers used HSV space extraction to classify fresh beef and bad beef. This research aims to develop a method for classifying fresh, medium and rotten beef using the HSV color space. This research produces accurate extraction results with appropriate classification of fresh and bad beef.